Mechanical Drying of Coffee: Influence of Operating Parameters on Cup Quality - Hurtado Cortés, Valeria; Orozco Blanco, Dayana Alejandra; Salas Calderón, Karen Tatiana; Ramón Ossa, Anyi Lorena; Bustos Vanegas, Jaime Daniel; Gutiérrez Guzmán, Nelson (Biotecnología en el Sector Agropecuario y Agroindustrial, 2024)
In the wet processing of coffee, it is crucial to control the drying operation to ensure the quality attributes developed during the fermentation stage. While solar drying is the most commonly used method, its low efficiency and difficulty in controlling process variables have led to the emergence of mechanical drying. This study assesses the impact of a static bed mechanical dryer's operating parameters (temperature, air flow, and coffee load) on drying time, physical defects, and SCA score. The treatments were also characterized by Fourier transform infrared spectroscopy (FTIR) and water activity. It was determined that air flow rates between 1,1 and 3,1 kg/min, coffee loads between 4 and 11 kg, and temperatures between 35 and 45 °C did not significantly impact the percentage of defects associated with drying, the SCA score, or the water activity of the coffee. Drying time was reduced by up to 50% when using 45 °C air temperatures. Additionally, agitation at low RPM and at one-hour intervals reduced drying time by 25 %.